Reuse of Uncured Carbon Fiber/Epoxy Resin Prepreg Scraps: Mechanical Behavior and Environmental Response - De Souza, Christiane Sales Reis; Opelt, Carlos Vinicios; Cândido, Geraldo Maurício; De Souza, Samia Danuta Brejao [UNESP]; Botelho, Edson Cocchieri [UNESP]; Fernandes Marlet, José Maria; Rezende, Mirabel Cerqueira (American Chemical Society (ACS), 2019)
This study aims to reuse the waste of uncured composite prepreg scraps from the ply cutting manufacturing process in the aerospace industry, avoiding the resin loss, waste disposal and expenses with its incineration.Carbon fiber/F155-epoxy resin laminates were produced by randomly positioned scraps, with different sizes and shapes, and characterized by tensile, compression, interlaminar shear (ILSS), and flexural tests. Tensile, compression, and flexural strengths of produced laminates decreased 13, 23, and 56%, respectively, compared to the same prepreg references. The ILSS test showed results 34% higher compared to the references. Higher specific strength (compression and tensile) was found in relation to a typical aircraft aluminum alloy. Therefore, the results opens a potential path to reuse uncured prepreg composite scraps to produce artifacts, as mold structures used in composites manufacturing, reducing the waste disposal in nature and contributing to sustainability.
Keywords: Carbon fiber; Mechanical properties; Prepreg; Recycling